KURIKULUM MERDEKA DALAM TINJAUAN FILSAFAT PENDIDIKAN - Sulalatun Nikma; Abd. Rozak (Qiro'ah : Jurnal Pendidikan Agama Islam, 2023)
The Merdeka Curriculum is a development of the K13 curriculum which focuses on aspects ofdeveloping the potential, talents, and interests of students through digitizing learning with the useof technology. This curriculum is a starting point for facing the Society 5.0 era whichpredominantly uses technology. The Merdeka Curriculum is compiled based on four schools ofeducational philosophy, each of which has characteristics that complement each other incurriculum preparation, only the dominance is different in each curriculum. The development ofan independent curriculum needs to be reviewed in terms of educational philosophy so that thedominance of this philosophy can be identified so that the output results are identified with thebasis of the curriculum. This research uses a qualitative method with a literature study approach(library research), primary sources are obtained from scientific literature and secondary sourcesare obtained from supporting sources, such as essays, papers, seminar results, and others. Theresults of this study are first, the perennialism school of philosophy does not dominate in theindependent curriculum because it is only used as a stronghold of cultural values so as not tocollapse in the modern era. Second, the essentialism school of philosophy dominates in the contentof learning materials. Third, the progressivism school of philosophy fills in the process of studentcharacter building through the Pancasila student profile. Fourth, the constructionism school ofphilosophy dominates the whole because of the renewal of the structure and system of schoolstakeholders